2011
DOI: 10.1038/aps.2011.99
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between cerebral state index and bispectral index as measures of electroencephalographic effects of sevoflurane using combined sigmoidal Emax model

Abstract: Aim:The cerebral state index (CSI) was recently introduced as an electroencephalographic monitor for measuring the depth of anesthesia. We compared the performance of CSI to the bispectral index (BIS) as electroencephalographic measures of sevoflurane effect using two combined sigmoidal E max models. Methods: Twenty adult patients scheduled for laparotomy were studied. After induction of general anesthesia, sevoflurane concentrations were progressively increased and then decreased over 70 min. An analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…In previous publications [ 24 , 28 , 29 ], an inhibitory sigmoidal model was used to describe the relationship between PSI and propofol dose in humans. However, other investigations performed under inhalant anaesthesia found that the dose-effect relationship of EEG-derived variables obtained from BIS and Narcotrend devices was better described with the combination of two fractional sigmoid E max models [ 26 , 27 , 30 , 31 ]. The same observation was made for PSI in pigs undergoing propofol anaesthesia in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous publications [ 24 , 28 , 29 ], an inhibitory sigmoidal model was used to describe the relationship between PSI and propofol dose in humans. However, other investigations performed under inhalant anaesthesia found that the dose-effect relationship of EEG-derived variables obtained from BIS and Narcotrend devices was better described with the combination of two fractional sigmoid E max models [ 26 , 27 , 30 , 31 ]. The same observation was made for PSI in pigs undergoing propofol anaesthesia in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation, the plateau was observed at PSI value of 44 (E max 2 = 44.2), which falls within the range generally targeted during surgical anaesthesia in humans (25–50). Former studies reported a plateau at around 40 for BIS and 50 for Narcotrend [ 26 , 27 , 30 , 31 ]. The value at which these indexes will tend to display a plateau over the range of anaesthetic doses tested depends on the computation algorithm, which is proprietary and often not published.…”
Section: Discussionmentioning
confidence: 99%
“…A similar plateau effect was reported for desflurane using BIS and Narcotrend 25 and for sevoflurane using BIS and Cerebral State Monitor (Danmeter A/S, Odense, Denmark). 26 In a secondary analysis following a large 1,100-patient cohort study (B-Unaware trial), 27 Whitlock et al found a -15.4 unit change (95% CI, -17.8 to -13.1) for every 1 MAC change in the 0.42-1.51 MAC range using the BIS monitor; yet, when the authors excluded patients with extreme values, this reduced to -8.6 unit per 1 MAC change.…”
Section: Correlation Of Wav Cns With Mac During Desflurane Anesthesiamentioning
confidence: 99%
“…CSI uses an algorithm different from that used for BIS. It has four sub-parameters derived from time domain analysis (burst-ratio) and frequency domain analysis (α-ratio, β-ratio, and β-ratio-α-ratio) of EEG [ 4 ].…”
Section: Introductionmentioning
confidence: 99%